Possessive Pronouns in German - Inggit Trisiana; Tatang Hariri (Universitas Negeri Malang, 2022)
This research describes possessive pronouns in German. This study aims to describe the form and functions of noun phrases with possessive pronouns in German. The data is obtained from short stories taken from the Onleihe Goethe Institute website. The result of this study is possessive pronouns in German are formed based on the pronouns of the person or owner and the number of owners. Meanwhile, the suffixes of the possessive pronouns are formed based on the number, the case, and the article of the nouns. The addition of suffixes does not occur only in possessive pronouns but also occurs in dative plural nouns. Possessive pronouns in sentences as a case marker, meanwhile, noun phrases with possessive pronouns function as the subject, object, and adverb.